ASPECTS OF DIAGNOSTIC ACTIVITIES IN PATIENTS WITH DYSFUNCTION OF TEMPOROMANDIBULAR JOINTS AND SIGNS OF BRUXISM - S. P. Rubnikovich; D. M. Borodin; Yu. L. Denisova; I. N. Baradina (Кубанский научный медицинский вестник, 2018)
Aim. The research was conducted to develop and implement the complex of diagnostic activities in patients with dysfunction of temporomandibular joints with signs of bruxism.Materials and methods. To achieve this aim we conducted a comprehensive diagnosis of 61 patients aged 20-29 years with bruxism and temporomandibular joints dysfunction (TMJD), the patients were divided into two groups. To diagnose and analyze the results of the disease treatment in patients we used a computer analysis with visualization of changes of the osteoarticular surface and parameters of the joint gap in the TMJ. Depending on the ratio of prognostic risk criteria and the development of bruxism, we distinguished the area of low, medium and high level of risk of disease progression.Results. Comparison of the treatment results of patients with bruxism from two groups in 12-24 months showed that patients from the second group had good treatment results. Patients of the second group underwent a complex of diagnostic activities and its data increased the treatment effectiveness. The results obtained from the treatment of patients from the first group indicate the lack of data from the standard examination of patients with bruxism.Conclusion. The developed complex diagnostic activities in patients with bruxism in combination with dysfunction of the TMJ and occlusive attrition of teeth allow to assess not only the local status but also to determine the functional state of dentoalveolar system and the cerebral cortex which affects the amount of therapeutic activities in the patient.